MODERNIZATION OF THE BANKING SECTOR IN UZBEKISTAN THROUGH DIGITAL TECHNOLOGIES - Mirzaeva Matluba Gaybulla kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: The article analyzes the processes of digital transformation in Uzbekistan’s banking system and their impact on financial stability. Based on statistical data for the period 2015–2024, the relationship between the introduction of digital services and key banking indicators was examined using regression analysis. The results show that the Digital Transformation Index has grown significantly, positively influencing banks’ Z-score and capital adequacy ratios. Moreover, the digitalization of financial services has been found to enhance service efficiency, reduce risks, and strengthen the overall stability of the banking system. The study identifies the development of digital infrastructure, government policy, and IT investments as the main drivers of change in the banking sector. However, it also highlights the relevance of regional digital disparities and cybersecurity challenges, proposing recommendations for their mitigation. This article serves as a valuable resource for banking professionals and policymakers, providing scientific insights to support strategic decision-making on digital transformation.